LIPID REQUIREMENTS OF MILKFISH {CHANOS CHANOS) FRY - Paulraj, R; Thirunavukkarasu, A R (Indian Journal of Fisheries, 2011)
Feeding axperiments conducted in the laboratory on the fry of milkfish,Chanos chanos, with purified diets containing graded levels of lipids showed that6%-lipid level induces the optimum food intake, maximum growth andbest utilization of food and protein. Whereas the lipid levels higher than thisoptimum have led to increased fat deposition in the tissues, the lower levelshave caused reduced growth and poor utilization of food and protein.An inverse relationship is observed between the moisture and lipid contents of theexperimental fish. The diet containing 6% lipid has provided the fish with 1.09%saturated fatty acids, 1.56% mono-unsaturated acids, and 3.195% of poly-unsaturatedfatty acids. The w6/w3 ratio of the diet was 2.43/0.762.